Assessing the efficacy and safety of pitavastatin compared to atorvastatin in dyslipidemic patients: a double blind randomized controlled trial - Patil, Chetan Y.; Baig, Mirza Shiraz; Doifode, Sudhkar M. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Statins are the first choice in the treatment of dyslipidemia, commonly atorvastatin. Pitavastatin is a newer statin with more potency, less drug interactions and many added advantages considering the longevity of treatment required for dyslipidemia. The objective of this study was to evaluate the efficacy and safety of pitavastatin versus atorvastatin in dyslipidemic patients associated with hypertension, diabetes and/or coronary artery disease. Methods: A prospective, comparative, randomized, controlled, double blind, clinical trial was designed. Total 100 eligible subjects were randomised into 1:1 ratio to receive pitavastatin 4 mg once daily and atorvastatin 20 mg once daily for period of 8 weeks. Evaluation was scheduled at 4 week and 8 week. The efficacy assessment included percentage change from baseline in various lipid parameters like low density lipoprotein cholesterol (LDLC), total cholesterol (TC), high density lipoprotein cholesterol (HDLC), triglycerides (TG), and LDLC/HDLC ratio. Results: Analysis of data showed a significant improvement in all lipid parameters within both therapeutic groups. The difference in LDLC, TC and TG levels was not statistically significant between the two treatment groups after 8 weeks of therapy. However, significant improvement was seen in HDLC and LDLC/HDLC ratio with pitavastatin as compared to atorvastatin at the end of the study. Both were well tolerated. Conclusions: With better HDLC levels, in addition to comparable efficacy and good tolerability of pitavastatin, as compared to atorvastatin, could be considered as good alternative for treatment of dyslipidemia.